THE COMPARISON OF FINANCIAL PERFORMANCE AND FINANCIAL DISTRESS ANALYSIS BETWEEN PT. HANJAYA MANDALA SAMPOERNA TBK WITH OTHER COMPANIES IN CIGARETTE INDUSTRY DURING COVID-19 PANDEMIC - Gabriela Yordanus, Putri
Starting at the end of 2019, the virus of SARS-Cov-2 or well known as Covid-19 spread all over the world causing changes in all aspects including economic and industries. This contagious disease forced people to keep their distance and contact within each other affecting increment on production cost, production and distribution delay, decreasing number of supply supported by new government rules regarding the pandemic situation, and contract payment delay due to low purchase power and low demand. It also lowered the utilization of workers and assets. During the pandemic, although purchasing power decreased, people still bought several things that were considered necessities and important including rice, cigarettes, chicken meat, chicken egg, mackerel, beef, and instant noodles. Even though cigarettes count as the second most bought object during the pandemic, PT Hanjaya Mandala Sampoerna as the market leader in Indonesia tobacco industry experienced a fall in their net income and increasing liabilities. Compared to other companies in industry, both PT Wismilak Inti Timur and PT Indonesian Tobacco manage to increase their net income although they also increased their liabilities during the pandemic. The other one, PT Gudang Garam also ran into net income decrease but they were able to lower their liabilities. Increasing liabilities is not always a bad sign since it costs less compared to the cost of equity. Therefore, this research aims to give clear financial performance of PT Hanjaya Mandala Sampoerna as the market leader who became the only company in the industry that experienced loss and rise in liabilities during the pandemic. It will give information regarding PT Hanjaya Mandala Sampoerna position among the industries and further development that could be done. It also shows PT Hanjaya Mandala Sampoerna financial position whether it nears the bankruptcy state due to the increasing liability and decrement of net income during the pandemic. The theories that are being used in this research are Altman Z-Score and financial ratios analysis that includes profitability ratio, liquidity ratio, debt ratio, and activity ratio. Altman Z-Score will be used to conduct a financial distress analysis to predict a bankruptcy state of a firm. While the financial ratios give information about financial performance of a company and allow the company to be compared with other companies in the same industry. The information used is gathered from each company’s financial statements in the form of secondary data. The data obtained from PT Hanjaya Mandala Sampoerna, PT Gudang Garam, PT Indonesian Tobacco, and PT Wismilak Inti Timur. From the analysis that has been conducted, PT Hanjaya Mandala Sampoerna indeed still leads the industry based on the financial performance despite increasing liabilities and income fall during the pandemic. Based on the Altman Z-Score analysis, PT Hanjaya Mandala Sampoerna is still far away in a safe position but each year it goes nearer to the bankruptcy zone. It indicates that several improvements could be done by PT Hanjaya Mandala Sampoerna to keep their financial stability. They can conduct research on other companies that manage to increase sales during the pandemic, improve their average collection period regarding the account receivables the company burdened, and finally conduct research concerning the fall on market price despite their good financial performance compared to other companies in the industry.